2019
DOI: 10.1097/pec.0000000000001256
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Hospital Trauma Team Activation Criteria for Children

Abstract: Objectives: Hospital trauma activation criteria are intended to identify children who are likely to require aggressive resuscitation or specific surgical interventions that are time sensitive and require the resources of a trauma team at the bedside. Evidence to support criteria is limited, and no prior publication has provided historical or current perspectives on hospital practices toward informing best practice. This study aimed to describe the published variation in (1) highest level of hospital trauma tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Determining appropriate triage is difficult, and there is a significant variation in triage criteria used across pediatric trauma centers. 47 At the study site, the current triage criteria could be refined by taking a closer look at Bravo encounters. We also identified an opportunity for improvement in patient flow.…”
Section: Discussionmentioning
confidence: 99%
“…Determining appropriate triage is difficult, and there is a significant variation in triage criteria used across pediatric trauma centers. 47 At the study site, the current triage criteria could be refined by taking a closer look at Bravo encounters. We also identified an opportunity for improvement in patient flow.…”
Section: Discussionmentioning
confidence: 99%
“…Although clear standards for undertriage and overtriage rates are not published, the benchmarks for field triage (<5% undertriage, or 1-sensitivity, and <35% overtriage, or 1-specificity) are often applied to in-hospital triage. The ACSCOT does not provide supporting evidence for mandating the use of the ACS-6 in pediatric trauma patients, and a 2019 systematic review by Drendel and colleagues 14 found considerable variability in published trauma team activation criteria and limited scientific justification for the use of the ACS-6. Clearly, the ACS-6 alone do not adequately identify children in need of the highest level of trauma center resources.…”
mentioning
confidence: 99%
“…Numbers of trauma patients may differ at similar-sized centers without level one status. It is well-known that the criteria for TTA vary among institutions (23), and different activation thresholds may result in considerable variation in the numbers of trauma calls. However, even for a designated level 1 center, the case load only adds up to two TTA per month, making major trauma an infrequent scenario.…”
Section: Discussionmentioning
confidence: 99%